Ocular manifestations and treatment safety in hepatitis C patients undergoing direct-acting antiviral therapy: a prospective cohort study - Guilherme Thomé de Carvalho; Carlos Eduardo Brandão Mello; Kelma Macedo Pohlmann Simões; Mário Martins dos Santos Motta; Max Kopti Fakoury; Bruno Vasconcelos Coimbra; Laura Gomes Nunes Melo; Flávio Mac Cord Medina (Revista Brasileira de Oftalmologia)
ABSTRACT Objective: To report the frequency of ocular manifestations in patients undergoing direct-acting antiviral therapy and assess treatment safety based on outcomes; to identify demographic variables associated with hepatitis C virus infection; evaluate treatment effectiveness through sustained virological response. Methods: A prospective cohort study was conducted involving chronic hepatitis C patients undergoing direct-acting antiviral therapy. Ophthalmological evaluations were conducted before treatment initiation and upon completion. Patients were advised to return in case of any visual symptoms. Results: The study comprised 30 patients, predominantly treated with sofosbuvir + velpatasvir. All patients achieved sustained virological response, and a notable improvement in fibrosis degree post-treatment was observed. No ocular complications attributable to direct-acting antiviral therapy were reported during the study. Conclusion: This study underscores the safety profile of direct-acting antiviral therapy concerning ocular manifestations. Demographic trends align with existing literature, and all patients achieved sustained virological response alongside improved liver fibrosis. These findings support the efficacy and safety of direct-acting antiviral therapy for hepatitis C patients.